Controversial role of laparoscopic appendicectomy vs steroids in a patient with provisional diagnosis of crohn’s disease: A case report (Indian Journal of Case Reports, 2020)
Crohn’s disease can originate in and be confined to the appendix, yet manifest clinical symptoms leading to the emergency laparoscopy. Preoperative radiologic findings can be similar to those of suppurative appendicitis. Here, we report the case of a 28-year-old female who had a provisional diagnosis of Crohn’s disease based on radiological finding but later on, diagnosed to have a perforated appendix.